(3SdGM GdSGdc hSO GdegGdcs - (3GdUhaj , eMeO Hf CHj GdaJM Gdahj GdeUQj, TeS GdOjf,J (B853 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fYe SdaJ , hGdMeO ddg Ydi fYe NdbJ hGdMeO ddg Ydi fYe XgQJ s
(3BNQgG (B:s
(3hdjS jOQcg HGdMhd eMJGdkG hGdYGQahf QLGdkG cdge s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B117s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B19s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs